Plantas utilizadas para tratamento da malária e males associados em comunidades indígenas no rio Uapés em São Gabriel da Cachoeira - AM - Trivellato, Cauê [UNESP] (2015)
Malaria is a disease that attacks three million people annually, and of these, one million people die annually. It is a disease poorly studied in the world. In Brazil, the affected region is the region of the Amazon rainforest. These populations, living in contact with malaria, have knowledge and information on ways to live with the disease and their ailments. So also have knowledge about the use of medicinal plants for the treatment of malaria and associated diseases. The objective of this study is to conduct ethnobotanical study of antimalarial plants by indigenous communities of the Uaupés River, a tributary of the Rio Negro. Between the years 2013-2015 interviews were conducted with 67 people, from conventional methodologies and participatory methodologies. As a result, 53 species of plants were identified for the treatment of malaria and related diseases. There is consensus between the use of Euterpe precatoria Mart., Euterpe caatinga Mart., Aspidosperma sp. and Amazonicus ampelozizyphus Ducke. The most cited botanical family was Arecaceae. The plants occur mainly in poultry, yard / garden and fields. It is used primarily the bark of plants, leaves and root followed. The main form of preparation is a decoction. The plants are primarily to cure malaria itself, and symptoms of fever and headache. All plants are managed. Knowledge comes from the older, but also of young leaders who seek knowledge in event / meetings / workshops. The use of participatory methodologies extended the exchange process with the communities.